2011
DOI: 10.1080/08927014.2011.585711
|View full text |Cite
|
Sign up to set email alerts
|

Competitive protein adsorption on polysaccharide and hyaluronate modified surfaces

Abstract: We measured adsorption of bovine serum albumin (BSA) and fibrinogen (Fg) onto six distinct bare and dextran- and hyaluronate-modified silicon surfaces created using two dextran grafting densities and three hyaluronic acid (HA) sodium salts derived from human umbilical cord, rooster comb and streptococcus zooepidemicus. Film thickness and surface morphology depended on HA molecular weight and concentration. BSA coverage was enhanced on surfaces upon competitive adsorption of BSA:Fg mixtures. Dextranization diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 57 publications
(83 reference statements)
5
26
0
Order By: Relevance
“…Dextrans were oxidized using the same procedure as described in our previous publications for silicon wafers [7;24;25;2832;41;42]. The dextranized surface for this experiment was obtained by oxidizing dextran for 0.5 hr, with additional methodological detail having been given previously [25;30]. Similarly, for hyaluronic acid modification, PU and PVC tubes were first aminated using 1,6-Hexanediamine 60 wt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dextrans were oxidized using the same procedure as described in our previous publications for silicon wafers [7;24;25;2832;41;42]. The dextranized surface for this experiment was obtained by oxidizing dextran for 0.5 hr, with additional methodological detail having been given previously [25;30]. Similarly, for hyaluronic acid modification, PU and PVC tubes were first aminated using 1,6-Hexanediamine 60 wt.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, our laboratories have demonstrated that silicon coated with either dextran or HA inhibits protein adsorption [28;30]. We have also shown that surfaces coated homogeneously or patterned with either dextran or HA, or coated with a binary pattern of dextran and HA, have differential effects for adhesion of human macrophages (THP-1 cell line) [41] and that cell morphology and secretory responses a substrate dependent [21].…”
Section: Introductionmentioning
confidence: 99%
“…28 On the contrary, hyaluronate is more hydrophilic and shows resistance to protein adsorption. 29 For this reason, we adhered CS as the final layer. AFM scanning was performed to observe the surface topography and measure the roughness, which in general exhibited an up-and-down evolution as well.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides and proteins are the major component of a conditioning layer. Sodium alginate widely exists in several of well-known algae and bacteria [35,36] and albumin has been chosen as typical protein for biofouling research [37]. In this paper, albumin/alginate was employed as the typical biomacromolecules to build a simplified model representing a conditioning layer.…”
Section: Introductionmentioning
confidence: 99%